2002
DOI: 10.1021/bm020079v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Chlorinated Microbial Polyesters

Abstract: Chlorination of microbial polyesters poly(3-hydroxybutyrate) (PHB) and poly(3-hydroxyoctanoate) (PHO) was carried out by passing chlorine gas through their solutions. The chlorine contents in chlorinated PHB (PHB-Cl) and chlorinated PHO (PHO-Cl) were between 5.45 and 23.81 wt % and 28.09 and 39.09 wt %, respectively. Molecular weights of the chlorinated samples were in the range of between one-half to one-fourth of the original values because of hydrolysis during the chlorination process. Thermal properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…That study revealed that as the extent of chlorination increased, the PHA changed from soft and sticky to crystalline, brittle, and hard. The chlorinated PHA would serve as a very useful intermediate for blending of polymers and for further modifications such as carboxylation …”
Section: Need For Chemical Modifications Of Phasmentioning
confidence: 99%
“…That study revealed that as the extent of chlorination increased, the PHA changed from soft and sticky to crystalline, brittle, and hard. The chlorinated PHA would serve as a very useful intermediate for blending of polymers and for further modifications such as carboxylation …”
Section: Need For Chemical Modifications Of Phasmentioning
confidence: 99%
“…The unsaturated side chains containing double bonds offer potentials for functionalizing these mcl-PHAs with improved properties or extended applications through chemical modification, such as chlorination, 126,127 crosslinking, [128][129][130][131] carboxylation, 131,132 hydroxylation, 133,134 and epoxidation. [135][136][137][138][139][140][141] Such modifications for the pedant groups make these mcl-PHAs functional with unusual physicochemical and mechanical properties.…”
Section: Biosynthesis and Modification Of Mcl-phas From Glycerolmentioning
confidence: 99%
“…Like rubber, these PHAs were used for sulfur vulcanization to provide three‐dimensional network structures comprising a decrease of tensile modulus, tensile strength and tear resistance 34,35. Another example of chemically modified PHAs containing sulfur was the preparation of PHA sodium sulfate salts, which were obtained by treatment of chlorinated PHAs with sodium thiosulfate 36. However, the sulfur atoms of these PHAs were not incorporated biologically.…”
Section: Other Sulfur Containing Biopolymersmentioning
confidence: 99%